Evaluation of sex- and gender-based medicine training in post-graduate medical education: a cross-sectional survey study. Issue 1 (October 2016) - Kling, Juliana; Rose, Steven; Kransdorf, Lisa; Viggiano, Thomas; Miller, Virginia
Abstract Background Addressing healthcare disparities is a national priority for initiatives in precision and individualized medicine. An essential component of precision medicine is the understanding that sex and gender influence health and disease. Whether these issues are addressed in post-graduate medical education curricula is unknown. Methods A questionnaire was designed and administered to residents across the Mayo Clinic enterprise to assess current knowledge of sex and gender medicine in a large program of post-graduate medical education and to identify barriers and preferred teaching methods for addressing sex and gender issues in health and disease. Descriptive and qualitative thematic analyses of the survey responses were compiled and analyzed. Results Responses were collected from 271 residents (response rate 17.2 %; 54 % female; 46 % male). A broad cross-section of training programs on all Mayo Clinic campuses (Arizona, Minnesota, and Florida) was represented. Sixteen percent of the respondents reported they had never had an instructor or preceptor discuss how a patient's sex or gender impacted their care of a patient; 55 % said this happened only occasionally. Of medical knowledge questions about established sex- and gender-related differences, 48 % were answered incorrectly or "unsure." Qualitative thematic analysis showed that many trainees do not understand the potential impact of sex and gender on their clinical practice and/or believe it does not pertain to their specialty. A higher percentage of female participants agreed it was important to consider a patient's sex and gender when providing patient care (60.4 vs. 38.7 %, p  =  0.02), and more male than female participants had participated in research that included sex and/or gender as a variable (59.6 vs. 39.0 %, p  < 0.01). Conclusions Curriculum gaps exist in post-graduate medical training regarding sex- and gender-based medicine, and residents often do not fully understand how these concepts impact their patients' care. Reviewing the definition of sex- and gender-based medicine and integrating these concepts into existing curricula can help close these knowledge gaps. As the practice of medicine becomes more individualized, it is essential to equip physicians with an understanding of how a patient's sex and gender impacts their health to provide the highest value care.